Transcriptomic and Proteomic Profiling of Tumor Microenvironment: Implications for Immunotherapy - Sayyed Usman Hashmi; Faisal Sarwar Abbasi; Aisha Qaiser; Atif Munir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The tumor microenvironment (TME) critically influences cancer progression and therapeutic outcomes, particularly in immunotherapy. Despite advances in checkpoint inhibitors, resistance persists due to the complex interplay of tumor, immune, and stromal components. Multi-omics approaches, including transcriptomics and proteomics, provide comprehensive insights into these regulatory networks. Aims & Objective: This study aimed to characterize transcriptomic and proteomic alterations within the TME to identify key immune-regulatory pathways, biomarkers, and potential therapeutic targets relevant to precision immuno-oncology. Methodology: Tumor and adjacent normal tissues were collected from cancer patients (n=60). Bulk RNA sequencing and single-cell RNA sequencing were performed to capture global and cell-specific gene expression changes. Proteomic profiling was conducted using LC–MS/MS. Data integration employed bioinformatic pipelines combining differential expression, pathway enrichment, and protein–gene correlation analyses. Selected biomarkers were validated by immunohistochemistry and ELISA. Results & Findings: Transcriptomic profiling revealed significant upregulation of immune checkpoints (PD-L1, CTLA-4), angiogenic mediators (VEGFA), and immunosuppressive cytokines (IL-10, TGFB1), with concurrent downregulation of antigen presentation genes (HLA-A, HLA-B). Single-cell analysis demonstrated enrichment of exhausted CD8+ T cells, regulatory T cells, and M2-like macrophages. Proteomic analysis confirmed elevated PD-L1, Galectin-9, and VEGFA expression, while showing reduced MHC class I proteins. Integrated pathway mapping indicated convergence on JAK/STAT, TGF-β, and VEGF signaling pathways, establishing a multifactorial immune-evasive TME. Conclusion: This integrative multi-omics study reveals coordinated transcriptional and proteomic programs that underpin immunosuppression within the TME. The findings underscore the limitations of monotherapy with checkpoint inhibitors and support rational combination strategies targeting cytokine, angiogenic, and antigen-presentation pathways. The identified biomarkers provide a foundation for precision immunotherapy and biomarker-guided clinical decision-making.